Air Leak Syndrome in Two Very Preterm Infants Born to Mothers with Coronavirus Disease 2019: An Association or a Coincidence? - Ajay Reddy; Krystin Engelhardt; Deepak Jain (Thieme Medical Publishers, Inc., 2020)
The novel coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mostly affects adults with limited information on possible vertical transmission from pregnant mothers. We present here two very preterm infants born to mothers with COVID-19, whose respiratory course was significant for initial mild respiratory distress syndrome who developed acute onset severe air leak syndrome at approximately 24 to 36 hours of age requiring thoracentesis. Their respiratory status improved gradually with resolution of air leak and respiratory failure by 2 weeks of age. Both infants tested negative for SARS-CoV-2 by reverse transcriptase-polymerase chain reaction of multiple respiratory specimens collected beyond 24 hours after birth. As the incidence of severe air leak syndrome is relatively low in preterm infants without risk factors, this presentation in two very preterm infants born to mothers with COVID-19 is intriguing and needs to be further evaluated in larger cohorts. If confirmed, this data could potentially be the first step toward generating hypotheses for mechanisms of lung injury, intrauterine transmission, or how to detect COVID-19 in preterm infants. In addition, these data will be critical for developing evidence-based guidelines for perinatal management of these infants as we continue to battle against the COVID-19 pandemic for the foreseeable future.